(untitled) (International Congress on Economics, Management and Business Studies, 2026)
This scientific article examines the theoretical-methodological and practical aspects of improving the use of artificial intelligence (AI) technologies in the credit activities of commercial banks. The acceleration of digital transformation in the global economy and increasing competition in financial markets require the modernization of banking services. In this context, AI technologies are becoming an important tool for improving lending efficiency, reducing credit risks, and enhancing the quality of customer service.